Is Neurofeedback therapy beneficial for Attention Deficit Hyperactivity Disorder? - Dwidjo Saputro (HM Publisher, 2021)
Attention-deficit hyperactivity disorder is a biological disease in brain function that is chronic, which results in the function of regulating response and decision making (executive function) not following the child's age development. Pharmacological therapy, especially methylphenidate, is still the primary therapy, even though it is not responsive to drugs. Multimodal therapy is a recommended therapy for ADHD treatment in Europe and the United States, which includes psycho-pharmaceutical therapy, behavioural therapy and family psycho-education. The administration of behaviour therapy alone does not provide satisfactory results, especially for long-term effects. Neurofeedback therapy is a form of behavioural therapy, with the principle of operant conditioning, which aims to train and condition the brain, with feedback from the brain's electrical waves. This paper aims to explain how far the benefits of neurofeedback therapy for people living with ADHD are based on available research data from the latest research results.